Stress conditions in the host induce persister cells and influence biofilm formation by Staphylococcus epidermidis RP62A - Fraiha, Rafael Ovando (2019)
INTRODUCTION: Studies have demonstrated that pathogens react to the harsh conditions in human tissues by inducing mechanisms that promote survival. METHODS: Persistence and biofilm-forming ability were evaluated during stress conditions that mimic those in the host. RESULTS: Carbon-source availability had a positive effect on Staphylococcus epidermidis RP62A adhesion during hypoxia, accompanied by a decrease in pH. In contrast, iron limitation led to decreased surface-adherent biomass, accompanied by an increase medium acidification and lactate levels. Interestingly, iron starvation and hypoxia induced persister cells in planktonic culture. CONCLUSIONS: These findings highlight the role of host stress in the virulence of S. epidermidis.